A study on the relationship between yoga exercise intervention and the comprehensive well-being of female college students - Liu, Lanjuan; Liu, Dandan; Liu, Cheng; Si, Yanran (Frontiers in Psychology, 2024)
Background: Due to the influence of theories, tools, and methodologies in studying well-being, sports science has predominantly focused on subjective well-being, with less attention given to psychological well-being and even less to the integrated study of comprehensive well-being. This study aims to analyze the relationship between yoga exercise intervention and the comprehensive well-being of college students and to explore the mechanism of a yoga exercise intervention to improve the comprehensive well-being of female college students. Objective: This study aims to analyze the relationship between yoga exercise intervention and the comprehensive well-being of female college students and to explore the mechanism of a yoga exercise intervention to improve the comprehensive well-being of female college students.Methods: With 92 female college students as subjects, the "Comprehensive Well-being Scale" was used, and research methods such as yoga exercise intervention, questionnaire surveys, qualitative analysis, expert interviews, and statistical analysis were employed to investigate the role of a yoga exercise intervention on the comprehensive well-being of female college students.Results: Among the nine dimensions of comprehensive well-being, the three dimensions of subjective well-being and the two dimensions of psychological well-being (health concern and personality growth) of female college students were significantly improved. Additionally, four other dimensions of psychological well-being also showed significant improvement. Furthermore, the improvement in the life satisfaction of female college students' subjective well-being was mainly achieved through yoga meditation, while partner yoga posture practice could help individuals gradually form a stable pattern of altruistic behavior.Conclusions: Yoga exercise intervention can improve the comprehensive well-being of female college students and can be an effective counseling method for college students' mental health education.